1998
DOI: 10.1046/j.1365-2923.1998.00156.x
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of a computer-aided learning package for minor oral surgery teaching

Abstract: 'Aspects of Minor Oral Surgery' is a highly interactive software program that was commissioned by the Department of Health, England, as part of the continuing education opportunities of general dental practitioners. The content of the program is also suited to the education of senior clinical dental students. The beta (pre-release) version was evaluated by 67 general dental practitioners, who completed a questionnaire on aspects of the program's functionality. Responses on its usefulness as an educational tool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…In this context veterinary medicine has some unique requirements and videos have been used to highlight safe animal handling [1,2], species-specific welfare issues [16] and disease [17,6]. Other reported uses of video technology in veterinary medicine are comparable with other fields of medicine, such as use in anatomy and surgery [18,19] and pathology [20] teaching.…”
Section: Introductionmentioning
confidence: 99%
“…In this context veterinary medicine has some unique requirements and videos have been used to highlight safe animal handling [1,2], species-specific welfare issues [16] and disease [17,6]. Other reported uses of video technology in veterinary medicine are comparable with other fields of medicine, such as use in anatomy and surgery [18,19] and pathology [20] teaching.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, the rapid development and spread of PCs and the internet have caused an increase in the number and variety of learning and software programs for medical education [17]. Several studies have shown that the interactive use of multi-media components and computer-based software can successfully be used in medical education to facilitate the learning process [8,10,16,19,21].…”
Section: Introductionmentioning
confidence: 99%
“…A review of the literature shows that compared to other medical specialties, computer-based training in Trauma and Orthopaedic Surgery is still in its infancy [12,14,18,19]. In 2003, the German medical licensing board demanded that changes be made in the medical curriculum.…”
Section: Introductionmentioning
confidence: 99%
“…The University of Birmingham program 'Aspects of Minor Oral Surgery' provides multimedia education in the field of oral surgery (Matthew et al, 1998). Some 77% of the students who used the program preferred this method to the use of video material, 69% preferred it to studying from a book, and 80% found it superior to research in the relevant journals.…”
Section: Introductionmentioning
confidence: 99%